A computational method for free terminal time optimal control problem governed by nonlinear time delayed systems - Chai, Qinqin; Wang, Wu (Applied Mathematical Modelling, 2018)
•A free final time optimal control problem for nonlinear delay systems is considered.•A solving method based on fully informed particle swarm optimization is adopted.•A practical optimal fishery control problem is solved. This paper considers a free terminal time optimal control problem governed by nonlinear time delayed system, where both the terminal time and the control are required to be determined such that a cost function is minimized subject to continuous inequality state constraints. To solve this free terminal time optimal control problem, the control parameterization technique is applied to approximate the control function as a piecewise constant control function, where both the heights and the switching times are regarded as decision variables. In this way, the free terminal time optimal control problem is approximated as a sequence of optimal parameter selection problems governed by nonlinear time delayed systems, each of which can be viewed as a nonlinear optimization problem. Then, a fully informed particle swarm optimization method is adopted to solve the approximate problem. Finally, two free terminal time optimal control problems, including an optimal fishery control problem, are solved by using the proposed method so as to demonstrate its applicability.